Makna Kesetiaan dalam Perjanjian Allah: Analisis Kontekstual Kitab Hosea - Joko Priyono; Andarias Pangngaroan; Rahel Rati Sarungallo (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2024)
This study examines God's faithfulness in the book of Hosea by highlighting its relationship to covenant theology, which is at the heart of God's relationship with His people. The book of Hosea depicts God's faithfulness through the symbolism of Hosea's marriage to Gomer, which reflects a loving and forgiving relationship amidst the unfaithfulness of the people. This study seeks to fill the gap of previous research that has mainly focused on the symbolic aspect of Hosea's story, emphasising the theological meaning of God's faithfulness in the covenantal context. Through the literature review method, this study explores the nature of God's faithfulness, its relationship to covenant theology, and its implications for Christian faith. The findings show that God's faithfulness goes beyond formal attachments, involving a deep love that restores unfaithful people. The research affirms that God's faithfulness is the basis of restoration and hope, which is culminated in the fulfilment of the covenant through Jesus Christ.